Elderly onset of MELAS in a male: A case report - Diao, Sheng-Peng; Chen, Song-Fa; Liu, Ai-Qun; Zhou, Zhi-Hua; Peng, Zhong-Xing; Hong, Ming-Fan (Frontiers in Neurology, 2022)
Background: Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) is one of the most common maternally inherited mitochondrial diseases which rarely affects elderly people. Case presentation: We report the case of a 61-year-old male MELAS patient. He was experiencing acute migraine-like headaches as the first symptoms. Laboratory data showed elevated lactate and creatine kinase levels. Brain magnetic resonance imaging (MRI) found a high signal intensity lesion in the left occipital-temporal-parietal lobe on diffusion-weighted imaging (DWI). Magnetic resonance angiography (MRA) revealed reversible vasoconstriction of the middle cerebral arteries and superficial temporal arteries. Muscle biopsy suggested minor muscle damage. A genetic study revealed a mitochondrial DNA A3243G mutation. Conclusions: Elderly onset MELAS is rare and easily misdiagnosed as ischemic stroke. MELAS with the onset of stroke-like episodes should be considered in adult or elderly patients with imaging findings that are atypical for cerebral infarction. Clinical diagnosis of MELAS could benefit greatly from the use of multimodal MRI.